Alloimmunization and autoimmunization among multitransfused thalassemia and sickle cell disease patients - Sangeeta Pahuja; Piali Mandal (Elsevier, 2024)
Blood transfusion is the mainstay for management of hemoglobinopathies, including thalassemia and sickle cell disease (SCD). Apart from other transfusion related adverse effects, immunization is a significant complication, particularly in multitransfused recipients. Alloimmunization rates vary widely, both in thalassemia and SCD patients. Alloimmunization complicates the management in form of hemolytic transfusion reactions, difficulty in finding compatible units, delays in transfusion and increasing costs. Exact pathogenesis and prevention modality have not been elucidated. Apart from antigenic differences, immunomodulatory effects and inflammation also play a role in pathogenesis. Ethnic heterogeneity between donors and recipients predisposes to higher alloimmunization.Transfusion management of hemoglobinopathies across the globe is fragmented, with different levels of care. Guidelines propose red cell antigen profiling, transfusion of leucoreduced red cells, preferably matched for Rh and Kell antigens, over and above ABO-D matching. For alloimmunized patients, corresponding antibody negative red cells need to be transfused. However, patients from different backgrounds are variably transfused with whole blood/red cells, which may or may not be leukoreduced. Prophylactic antigen matching reduces the risk of alloimmunization, however, has limitations. RH variants may not be picked up by phenotyping alone. Moreover, the approach of prophylactic antigen matching is expensive, labour intensive, time consuming and may cause delays in transfusions. There is limited, low quality evidence on best practices for transfusion management of SCD and thalassemia. The review analyses the magnitude of problem, factors contributing and modalities for prevention and management of immunization.